How network coding system constrains packet pollution attacks in wireless sensor networks. (1st January 2013) - Zhang, Yuanyuan; Minier, Marine
Packet pollution attack is considered as the most threatening attack model against network coding-based sensor networks. A widely held belief says that, in a single source multidestination dissemination scenario, the total number of polluted packets in the network will grow with the length of the transmission path and the decoding failure (DF) rate at the further destination nodes are relatively lower. In this work, we first obtain an opposite result by analysing the pollution attack in multicast scenarios, and find out a convergence trend of pollution attack by network coding system, and quantify the network resiliency against the pollution attacks which happen at any place along the source-destination paths. Then, the analysis result is proved by our simulations on two most widely deployed buffer strategies, Random-In Random-Out (RIRO) and First-in First-Out (FIFO). Finally, it is proved that RIRO has a much advanced security feature than FIFO in constraining the pollution attack gradually, and almost vanished in the end.